Greenland - Blashfield, Jean F. (New York : Children's Press, 2005)
Discusses the geography and climate, history, wildlife, economy, government, people, religion, and culture of the island nation of Greenland.
North of everywhere -- Green and white -- Alive on land, ice, and sea -- Greenland's story -- Matters of government -- Making a living -- Inuit and Dane -- Shamans and cathedrals -- Kayaks and crafts -- Living on ice -- Timeline.
Includes bibliographical references (p. 134), filmography, and index.
5.3
5-8
Keywords: Greenland -- Juvenile literature; Greenland; Greenland